TINJAUAN HUKUM TERKAIT TAWARAN KREDIT TANPA AGUNAN (KTA) MELALUI SHORT MESSAGE SERVICE (SMS) - Sundari, Sundari; Fitriah, Fitriah (Faculty of Law, University of Palembang, 2022)
Related to Short Message Service (SMS) received from banks actually the government has provided protection for consumers of telecommunication service users, among others through the Regulation of the Minister of Communication and Informatics No. 5 of 2021 on the Implementation of Telecommunications (Permenkominfo 5/2021) which stipulates that telecommunication service providers must store telecommunication service customer data as long as telecommunication service customers actively subscribe to telecommunication services. This research aims to see what steps can be legally taken if you feel disturbed by the credit without collateral (KTA) offer given through short messages such as SMS. The research method used in this study is a normative method of law. First, telecommunication service providers are also required to keep the data and /or identity of customers secret unless otherwise specified under the law. Second, violations of these provisions by telecommunication service providers will be subject to administrative sanctions that can be in the form of written reprimands, the imposition of administrative fines, temporary suspension of attempted activities, termination of access, police force, revocation of services; and/or, revocation of the permit attempts.